Fertilizer in Ethiopia: An assessment of policies, value chain, and profitability - Rashid, Shahidur; Tefera, Nigussie; Minot, Nicholas; Ayele, Gezahegn (International Food Policy Research Institute, 2013)
The study involved interviewing a large number of stakeholders in fertilizer value chain, collection of data on costs and margins from the key actors in the value chain, as well as household survey data. In this paper, we present the key findings from that study. In particular, the paper presents estimates of detail costs and margins in the value chain, econometrically derived profitability and yield responses, and the costs of government’s fertilizer promotion policies. Based the estimates of the costs and margins in the fertilizer value chain, the study argues that the current value chain will not be sustainable unless the scale of operation, as well institutional capacity, of the primary cooperatives goes up.